Tackling the Bullies in Academe - Jorg Waltje PhD; Laura Trujillo-Jenks PhD (Academic Chairpersons Conference Proceedings, 2017)
Severely hurtful and undermining behavior is on the increase at university campuses, partly due to the widespread jealousy and competition that is naturally prevalent in higher education. This interactive workshop will provide strategies for chairs who have to deal with difficult faculty, but it will also point out ways to create a departmental atmosphere of civility and collegiality in which bullies cannot thrive. We will use case studies to analyze realistic scenarios that can later be used by chairpersons to encourage discussions on plans of action and solutions in their home departments.
Keywords: bullying; case studies; collaboration; leadership; solutions